Fünfundzwanzig arabische Geschäftsdokumente aus dem Rotmeer-Hafen al-Quṣayr al-Qadīm (7./13. jh.) [p.quseirarab. ii] - Kaplony, Andreas (Islamic history and civilization : studies and texts, 2014)
The 'Qusayr Documents', one of the few Arabic archives unearthed in situ, shed new light on a lonely 13th-century outpost on the Red Sea shore where Egyptian donkey caravans met with ships coming from the Hidjaz and South Arabia.0This is the publication of another twenty-five business letters and process slips from al-Qusayr al-Qadim. These unspectacular but elucidative documents follow clear rules in phraseology and in layout, as is shown by a multitude of close parallels with Arabic papyri and papers and with Judeo-Arabic Geniza-documents. The book includes a short introduction on how online-search strategies can be used in dealing with Arabic mass sources.00Die 'Qusayr-Dokumente', eines der wenigen in situ gefundenen arabischen Archive, werfen ein neues Licht auf einen einsamen Aussenposten an der Küste des Roten Meeres, in dem im 13. Jahrhundert ägyptische Eselskarawanen auf die Schiffe aus dem Hidjaz und Südarabien trafen.